『개벽』에 나타난 1920~1930년대 인도에 대한 조선의 인식 - 문예찬(Moon, Ye-Chan) (남아시아연구, 2024)
청일전쟁에서 청나라가 일본에게 패배하면서 조선에서 중화주의적 세계관이 붕괴되자 조선인들은 만국공법에 기초한 국제질서 속에 다양한 국가들에 대한 이해를 도모하기 시작하였다. 세계 지리와 세계사에 대한 지식이 조선에 보급되고 서양으로부터 다양한 사상과 정보가 유입되면서 조선의 지식인들도 점차 인도에 관심을 가지게 되었다. 다른 국가나 대상들과 마찬가지로 인도에 대한 인식도 다면적인 측면을 가진다. 그렇기에 인도에 대한 조선인들의 인식변화를 살펴보는 것은 당시의 조선인들이 가지고 있었던 세계관과 문제의식, 사회 변혁의 방향 등을 이해하는데 도움이 된다. 특히 일제의 강압적 통치를 경험하고 있던 식민지 조선의 현실에서 인도의 민족운동과 인도의 지도자들은 조선인들에게 큰 관심의 대상이 되었다. 일제강점기 인도에 대한 인식은 1920~1930년대 지식인들의 대표적인 잡지였던 『개벽』에서도 잘 드러난다. 『개벽』에는 초기에 인도에 대한 단순 사실이나 동양문명의 기원으로 추상화된 인도에 대한 서술이 주를 이루다가 점차 인도의 현재 정치적 상황과 사회 모습에 대한 구체적인 내용이 서술에 드러난다. 또한 『개벽』의 논자들은 인도의 문화, 종교, 제도 등의 후진성을 부각하며 조선의 근대화와 선진화의 필요성을 역설하였다. 그리고 이 과정에서 인도는 전근대와 비문명의 상징으로 활용되었다. 그러나 시간이 흐르면서 인도는 점차 같은 반제국주의 운동의 동반자이자 나아가 조선 사회가 본받아야 할 모범으로 인식되었다. 『개벽』의 각종 논설에서 인도인들은 세계 피압박민족의 대표로 설정되기도 하였으며, 심지어 인도의 상황을 조선의 상황보다 긍정적으로 평가하거나 동경하는 인식도 등장하였다. 이처럼 1920~1930년대 『개벽』에 나타나는 인도에 대한 조선 지식인들의 인식은 조선 내부의 정치적 상황, 논자들의 사상적 지향, 조선 독립운동의 방향성 내지 지향점에 따라 서로 다른 모습으로 다양하게 소환 또는 소비되었다. When the Qing Dynasty was defeated by Japan in the Sino-Japanese War and the china centric world view collapsed in Joseon, Koreans began to seek understanding of various countries in an international order based on Elements of International Law. As knowledge of world geography and world history spread to Joseon and various ideas and information flowed in from the West, Joseon intellectuals also gradually became interested in India. Like other countries or objects, perceptions of India also have multifaceted aspects. Therefore, looking at the changes in the Koreans perception of India in Japanese colonial era is helpful in understanding the world view and critical awareness of the Korean people at the time, and the direction of social change. In particular, in the reality of colonial Joseon, which was experiencing Japan's oppressive rule, Koreans became very interested in the Indian independence movement and its leaders. The perception of India during the Japanese colonial period is also clearly revealed in 『Gaebyeok』, a representative magazine for intellectuals in the 1920s and 1930s. 『Gaebyeok』 initially mainly consists of descriptions of India abstracted from simple facts about India or the origins of Eastern civilization, but gradually details about India's current political situation and social situation are revealed in the descriptions. In Addition, the authors of 『Gaebyeok』 pursued the need for modernization and advancement of Joseon, emphasizing the backwardness of India's culture, religion, and institutions. And in this process, India was used as a symbol of pre-modernity and uncivilization. However, as time passed, India was gradually recognized as a partner in the same anti-imperialist movement and as an example for Joseon society to follow. In various views ofeditorials in 『Gaebyeok』, Indians were set up as representatives of the world's oppressed peoples, and there was even a perception that the situation in India was evaluated more positively than that of Joseon, or Koreans also had a perception of longing for India. In this way, Joseon intellectuals’ perception of India in 『Gaebyeok』 in the 1920s and 1930s was summoned or consumed in various ways, depending on the political situation within Joseon, the ideological orientation of the writers, and the direction or orientation of the Joseon independence movement. KCI Citation Count: 0